PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE FIRING LINE TERHADAP KEMAMPUAN PENALARAN MATEMATIKA SISWA SMP - Arsita, Kadek Rika; Suarsana, I Made; Mertasari, Ni Made (JURNAL e-DuMath, 2018)
AbstractThis research aimed to determine the studentâs mathematical reasoning ability of 7th grade of SMP Negeri 6 Singaraja in learning with the active learning strategy of firing line. This type of research was a quasi-experiment with post-test onlycontrol group design. The population of this study was all students of class VII SMP Negeri 6 Singaraja. The sample was taken by cluster random sampling technique. Data on students mathematical reasoning abilities was obtained through a description test. Data analysis uses one-party t test that was right side. The result of the hypothesis was rejected and show that the ability of mathematical reasoning of 7th grade SMP Negeri 6 Singaraja which is taught by active learning strategy of firing line better than students who taught with conventional learning. It can be concluded that the active learning strategy of firing line has a positive effect on students mathematical reasoning ability.Keywords:active learning strategy of firing line, mathematical reasoning ability.